2005
DOI: 10.1007/s10722-004-5721-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure in Tunisian Apricot, Prunus armeniaca L., Populations Propagated by Grafting: A Signature of Bottleneck Effects and Ancient Propagation by Seedlings

Abstract: In order to give insights into the origin and historical selection process of Tunisian apricot propagated by grafting, 31 cultivars from three areas presenting contrasting ecological conditions -Kairouan, Testour and Ras Jbel were compared to cultivars from Europe, North America, North Africa, Turkey, Iran and China, using 234 AFLP markers. The phenetic analysis allowed to distinguish 5 clusters, the four previously defined groups: -'diversification', 'geographically adaptable', 'continental European' and 'Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
22
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 13 publications
11
22
2
Order By: Relevance
“…As expected, we noted a highly significant proportion of admixed accessions derived from seed propagated populations (68.3%) since gene flow can only occur when farmers propagate their apricots through seedlings. However, we observed a similar proportion of admixed accessions among graft (24%) and seed propagated apricots (21.7%), thus supporting the assumption that graft and seed propagated apricots share a common gene pool, as previously suggested in Tunisia (Khadari et al, 2006;Bourguiba et al, 2010) and the Maghreb region (Bourguiba et al, 2012a).…”
Section: Discussionsupporting
confidence: 89%
“…As expected, we noted a highly significant proportion of admixed accessions derived from seed propagated populations (68.3%) since gene flow can only occur when farmers propagate their apricots through seedlings. However, we observed a similar proportion of admixed accessions among graft (24%) and seed propagated apricots (21.7%), thus supporting the assumption that graft and seed propagated apricots share a common gene pool, as previously suggested in Tunisia (Khadari et al, 2006;Bourguiba et al, 2010) and the Maghreb region (Bourguiba et al, 2012a).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the Tunisian traditional apricot cultivars showed a relatively high level of polymorphism as compared with the Mediterranean materials. Moreover, our results confirmed the presence of a decreasing gradient of genetic diversity from East to West the Mediterranean area, which may be explained by bottleneck effects related to historical introduction and apricot propagation in Tunisia by numerous seedling events (Hagen et al 2002;Khadari et al 2006).…”
Section: Discussionsupporting
confidence: 79%
“…These results suggested that the genetic background of cultivars from the northern, central, and southern areas of apricot culture in Tunisia was close. The same results were revealed also by Khadari et al (2006), which showed that the Tunisian apricot cultivars represented a distinct group with a narrow genetic basis.…”
Section: Discussionsupporting
confidence: 71%
“…Such a loss of genetic diversity was significant when comparing clusters 1 (‘Iran-Caucasian’) and 3 (‘North Mediterranean Basin’) and clusters 1 and 4 (‘South Mediterranean Basin’). Nevertheless, it was not significant when cluster 3 was compared to cluster 4, despite the different modes of apricot propagation: vegetative in North Mediterranean vs. sexual reproduction in South Mediterranean, especially in the oasis agroecosystems in the Maghreb area [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…In North Africa ( Algeria, Morocco, and Tunisia), apricot germplasm contained accessions propagated by grafting, but also by seeds specifically located in oasian regions. A fine-scale genetic diversity study conducted using AFLP markers at the within-population level, focusing on Tunisian grafted apricot cultivars, supported the assumption of few introduced genotypes that have been firstly propagated by seeds [33]. Analysing a larger set of Tunisian apricots, including both vegetatively propagated cultivars and seed propagated accessions, Bourguiba et al [34] identified two main gene pools according to their propagation mode and confirmed the assumption that these two gene pools shared the same origin.…”
Section: Introductionmentioning
confidence: 99%